Community Participation in the Complete Systematic Land Registration Program (PTSL) in Rumbai District, Pekanbaru City - Wifa Inessya Lumban Gaol; Dadang Mashur (Journal of Education Technology Information Social Sciences and Health, 2024)
The Complete Systematic Land Registration Program (PTSL) is the government's effort to deal with land matters, especially in terms of granting land legality. Regulations regarding the PTSL program are included in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 6 of 2018 concerning Complete Systematic Land Registration. Rumbai District still faces obstacles in implementing PTSL due to the slow process of making land certificates. This research uses a qualitative research approach with a case study method with a research focus, namely describing community participation in the implementation of the PTSL program in Rumbai District, Pekanbaru City. Research is located at the Pekanbaru City Land Office and Rumbai District. Data collection uses interview, observation and documentation techniques. Data presentation and data analysis techniques are carried out by collecting data, reducing data, presenting data and drawing conclusions. The technique for testing the validity of data uses source triangulation. The concept used is the stages of community participation by Sutarta (in Tawai Yusuf, 2017). The research results show that community participation in the PTSL program has not been implemented well. The factors inhibiting community participation in Rumbai District, Pekanbaru City are a lack of transparency and less than optimal socialization. To increase community participation, Pekanbaru City BPN must be able to prioritize transparency in the implementation of PTSL as well as ongoing socialization